Palaeo-environments at the Batagay site in West Beringia during the late Quaternary - Ashastina, Kseniia (2018)
Permafrost deposits, which underlie vast areas of Asia, provide valuable information for reconstructing past ecological events. The syngenetic permafrost deposits of the Batagay outcrop preserve valuable data about the palaeo-environment of the Yana Highlands of inland Beringia. The former subcontinent of Beringia connected Eurasia and America during low sea-level stands and hosted a now extinct biomethe mammothsteppe. To unravel the environmental history of West Beringia, the Batagay permafrost sequence was investigated. The first part of the thesis reports the first sedimentological results and provides a stratigraphical and temporal framework of the sequence. The stratigraphy comprises five units, including two ice complexes, two sand units and one woody layer. OSL and AMS dating suggest that the sequence started to accumulate during the late Middle Pleistocene and extends through the Late Pleistocene, with interruptions and erosional events. The second part of the thesis presents the palaeo-environmental reconstruction at the Batagay site during marine isotope stages (MIS) 62. Plant macrofossil, palynological, entomological, and charcoal analyses were performed on the samples from the Batagay outcrop. Palaeontological data indicate that the Yana Highlands were a northern refugium for larch, steppe communities, and herbivores. That larch stands and meadow steppes persisted at the site from MIS 6 to 2 indicating environmental stability in the region. The third part of the thesis discusses the phylogeographical history of the endemic steppe plant Stellaria jacutica of the Last Interglacial age. A finding of this single seed suggests that modern steppes of the region did not establish as late as in the Holocene. Instead, they are relics of a formerly closed central Siberiannortheast Yakutian steppe belt. The data obtained from the inland Batagay outcrop provide valuable information about the evolution of vegetation in continental settings of West Beringia.